A critical review on fast-food consumption pattern among South Asian and Southeast Asian young adults - Arya, Chhavi; Dubey, Neha (International Journal Of Community Medicine And Public Health, 2023)
Fast food consumption trend has become very popular worldwide. Globalization has led to rapid rise in the number of fast-food outlets in Asian countries. The present study focuses on reviewing the consumption pattern of fast food among young adults of South Asian and Southeast Asian countries. Here a shift has been witnessed from consumption of traditional homemade food which included healthy nutritious locally available foods toward fast foods and processed foods. An extensive review of existing scientific studies in several South Asian and Southeast Asian countries was carried out to analyse fast food consumption patterns of young adults. Globalization, affluence, busy schedules, increase in number of working female population, mass media, increase in fast food production and delivery outlets are some of the main reasons contributing to increasing fast food consumption trends. Several western fast-food franchises are now well established in developing Asian countries. Dining out culture has increased in the Asian society and is socially acceptable. A rapid nutritional shift in Southeast Asia may be due to increase in food availability and food purchasing power. Consumption of fast-food items is associated with increasing obesity rates among young adults. Such trends are also associated with the increasing prevalence of non-communicable diseases such as indigestion, hypertension, asthma, and other several diseases among South Asian and Southeast Asian adults.